TRANSFORMATIONAL LEADERSHIP ANALYSIS OF PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS MEDIATION AT PT. MELIA SEHAT SEJAHTERA MEDAN - Yoan Yolanda; Abdul Rahim Matondang; Yeni Absah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to analyze the relationship between transformational leadership, organizational commitment, and member performance at PT Melia Sehat Sejahtera, Medan. The method used is an associative method with a quantitative approach, which aims to examine the relationship between variables with a research population of 300 members, using a sample of 172 members. The data analysis technique used is Structural Equation Modeling with Partial Least Square (SEM-PLS). The research results show that transformational leadership has a significant influence on organizational performance. Apart from that, transformational leadership also contributes significantly to team member commitment. The commitment of team members themselves has been proven to have a very significant influence on performance. Path analysis shows that the combination of transformational leadership and team member commitment has a significant impact on performance, indicating that team member commitment mediates the relationship between transformational leadership and performance.